Stomatal Arrangement Pattern: A New Direction to Explore Plant Adaptation and Evolution - Liu, Congcong; Li, Ying; Xu, Li; Li, Mingxu; Wang, Jianming; Yan, Pu; He, Nianpeng (Frontiers in Plant Science, 2021)
The arrangement patterns of stomata on the leaf surface influence water loss and CO2 uptake via transportation and diffusion between stomata, the sites of photosynthesis, and vasculature. However, the quantification of such patterns remains unclear. Based on the distance between stomata, we developed three independent indices to quantify stomatal arrangement pattern (SAP). “Stomatal evenness” was used to quantify the regularity of the distribution of stomata based on a minimum spanning tree, “stomatal divergence” described the divergence in the distribution of stomata based on their distances from their center of gravity, and “stomatal aggregation” was used to quantitatively distinguish the SAP as clustered, random, or regularly distributed based on the nearest-neighbor distances. These three indices address the shortcoming of stomatal density that only describes “abundance” and may, collectively, have a better capacity to explore crop development, plant adaptation and evolution, and potentially ultimately enable a more accurate reconstruction of the palaeoclimate.